A compact peanut-shape printed antenna for bio-telemetric tablet system - M. S., Zulkefli; Mohd Fareq, Abd Malek, Dr.; Mohd Hafizuddin, Mat; Ronald, Suzanna Harun; Mohd Faizal, Jamlos, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/